Locus of control and life satisfaction - López Ibáñez, Elisardo; Ruiz-Herrera, Noelia (Pensando Psicología, 2024)
Objective: To explore the relationship between locus of control and life satisfaction in a sample of Spanish residents.Method: A sample of 231 participants (42% women, 52% men) was assessed with the Locus of Control Scale (Rotter, 1966) and the Satisfaction with Life Scale (Diener et al., 1985) using Google Forms. This was a correlational, non-experimental, cross-sectional design.Results: 1) People with higher internal locus of control showed more satisfaction with their lives; 2) internal locus of control was higher with increasing income level; 3) women scored higher on external locus of control than men.Conclusions: The findings suggest including locus of control as one of the factors to be considered in therapeutic strategies aimed at improving people’s well-being.
Keywords: locus of control; satisfaction with life; adults; spanish sample